please yaar factorise kar ke de do na yaar please(♡˙︶˙♡)
Attachments:
![](https://hi-static.z-dn.net/files/d35/604365ef0bd325b907fc912951e32047.jpg)
Answers
Answered by
0
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/df3/27ffdd2d23e0834efafcc54d7cd70f30.jpg)
Answered by
1
Answer:
4(x - 3y)(x + 6y)
Step-by-step explanation:
(2x + 3y)^2 - (9y)^2
=> (2x + 3y)^2 - (3y)^2
a^2 - b^2 = (a + b)(a - b)
=> (2x + 3y + 3y)(2x - 3y - 3y)
=> (2x + 12y)(2x - 6y)
=> (2x - 6y)(2x + 12y)
=> 2(x - 3y) * 2(x + 6y)
=> 4(x - 3y)(x + 6y)
#MarkAsBrainliest
Similar questions